Potential Benefits of Pre-emptive PGx Testing in Male Breast Cancer Patients - Heather Randles; Nina Abraham; Michael J. Schuh (University of Minnesota Libraries Publishing, 2019)
The objective is to report a case of recurrent breast cancer in a poor CYP2D6 metabolizer male patient on tamoxifen, and how pharmacogenomic (PGx) testing can play an important role in selecting appropriate adjuvant endocrine therapy. The case examined here is a 60-year-old white male diagnosed with recurrence of breast cancer. The patient was prescribed tamoxifen four years prior as adjuvant endocrine therapy after initial treatment with surgery. PGx testing ordered at the time of recurrence revealed patient is a poor metabolizer of CYP2D6, which may decrease the efficacy of tamoxifen. The results prompted a change in therapy to an aromatase inhibitor (AI). This case illustrates the potential benefits of preemptive PGx testing in a male breast cancer patient to assist in selecting appropriate adjuvant therapy based on how the patient metabolizes medications. In addition, PGx testing encourages patient involvement by emphasizing the association of genetics in determining treatment. The ultimate goal in performing these tests is to individualize treatment to improve safety and efficacy while minimizing adverse drug reactions.   Article Type: Case Study